Installation and configuration of wireless networks Low cost wireless network with Matlab standalone application - Serrano, Joana (2014)
The need to monitor sensors it is urgent in several areas of science, this is achievable using wireless technology. Wireless technology has to be present in this issue in order to provide flexibility. ZigBee devices, the low cost wireless technology, are becoming an important asset in sensor monitoring. These smart devices are able to operate for long periods of time without any maintenance needed. Our work was made in the instrumentation field, with the purpose of designing a standalone application that monitor sensors via wireless, a reliable and efficient application using MATLAB software as our work present.